Extracorporeal Membrane Oxygenation and Lebanese Critical Care Nurses' Perceptions: A Qualitative Phenomenological Study - Ali Salloum MSN, RN; Mirna Fawaz PhD, MSN, RN; Ahmad Rayan PhD, MSN, RN; Shaher H. Hamaideh PhD, MSN, RN; Salam Bani Hani PhD, MSN, RN; Mohammed ALBashtawy PhD, MPH, RN; Ahmad M. Al-Bashaireh PhD, MSN, RN; Omar M. Khraisat PhD, MSN, RN; Haitham Khatatbeh PhD, MSN, RN; Abdullah Alkhawaldeh PhD, MSN, RN; Asem Abdalrahim PhD, MSN, RN; Sa'd ALBashtawy MD (SAGE Publishing, 2023)
Introduction The training of nursing staff to deliver extracorporeal membrane oxygenation in Lebanon has recently attracted attention. It is important to comprehend the background of nurses who take on this new duty. Objectives The main objectives of this study were to (1) explore the experiences of intensive care unit nursing staff who work with extracorporeal membrane oxygenation, (2) identify the psychological and physiological challenges experienced by intensive care unit nurses while managing patients with extracorporeal membrane oxygenation, and (3) determine the roles assumed by intensive care unit nurses while managing patients utilizing extracorporeal membrane oxygenation. Methods A qualitative phenomenological design utilizing semistructured interviews utilizing a purposive sampling of 15 intensive care unit nurses using extracorporeal membrane oxygenation devices. Interviews were audio recorded, verbatim transcribed, and thematically analyzed. Results Three themes emerged, namely (1) nurses' role in extracorporeal membrane oxygenation, (2) skills and training, and (3) challenges faced by extracorporeal membrane oxygenation nurses. Conclusion This study demonstrates that nurses play a crucial role in providing extracorporeal membrane oxygenation patient care, placing them under significant occupational stress due to the intensive care unit's routine workload and the demands of extracorporeal membrane oxygenation. Additionally, role confusion brought on by a lack of professional practice norms and emotional exhaustion made occupational pressure worse.